The relevance of social capital and sense of coherence for mental health of refugees. (December 2022) - van Sint Fiet, Antoine; de la Rie, Simone; van der Aa, Niels; Bloemen, Evert; Wind, Tim
Abstract: Introduction: Migration puts refugees in a completely new social context when simultaneously some have to deal with previously experienced traumatic events and post-migration stressors. Social capital and sense of coherence could be key resources to improve mental health of refugees. This study aims to examine the interplay between social capital (structural and cognitive), sense of coherence and mental health of refugees in the Netherlands. Objective: The present study was conducted to i) examine if social capital (structural and cognitive) and mental health are related in a population of Dutch refugees, and ii) test if sense of coherence has a moderating and/or a mediating effect on this relation. Method: Data were collected through questionnaires (n = 154) in a cross-sectional survey at different locations throughout the Netherlands. The data were analysed with multiple regression analyses and nonparametric bootstrapping using SPSS. Results: Social capital (structural and cognitive) was positively related to mental health. In addition a positive relation between sense of coherence and mental health of refugees was found. The relationship between cognitive social capital and mental health was completely mediated by sense of coherence. No moderation effect of sense of coherence on the relation between social capital and mental health was found. Conclusions: The current study contributed to understanding the social mechanism that determines refugee mental health: participating in social groups (structural social capital) and having supportive and trusting relationships (cognitive social capital), whilst experiencing life as comprehensible, manageable, and meaningful (sense of coherence) are positively related to better mental health of refugees. Findings indicate that preventive interventions aiming to enhance refugees' mental health may be more effective when targeting and promoting both social capital and sense of coherence, from a relatively early stage after arrival in the Netherlands. Highlights: Structural and cognitive social capital are positively related to mental health of refugees. A positive relation is found between sense of coherence and mental health of refugees. Sense of coherence mediates this relation between cognitive social capital and mental health. Including resiliency factors and strengthening social mechanisms may create more effective mental health interventions.